Tafsir dan Budaya Aceh - Iskandar Usman (TAFSE: Journal of Qur'anic Studies, 2021)
This paper aims to examine the development of interpretation in Aceh. This research is qualitative with documentation data collection techniques and uses descriptive-analytical methods by looking at the literature and scientific history in Aceh. The results showed that the study of interpretation in Aceh was not as developed as fiqh. There was even a long vacuum after the book Turjuman al-Mustafid written by Abdurrauf al-Singkili. Sometime later, the works of scholars began to appear who began to focus on studying and writing about the interpretation of the Qur'an. Tulisan ini bertujuan untuk mengkaji fenomena perkembangan tafsir di Aceh. Penelitian ini bersifat kualitatif dengan teknik pengumpulan data dokumentasi dan menggunakan metode deskriptif analitis, dengan melihat literatur dan sejarah keilmuan di Aceh. Hasil penelitian menunjukkan bahwa kajian tafsir di Aceh tidak terlalu berkembang sebagaimana fikih. Bahkan ada kevakuman yang lama setelah kitab Turjuman al-Mustafid yang ditulis oleh Abdurrauf al-Singkili. Beberapa masa setelahnya, mulai muncul karya-karya ulama yang mulai fokus mengkaji dan menulis tentang tafsir al-Qur’an.